UPAYA INDONESIA MEWUJUDKAN DRUG-FREE ASEAN 2015 - Letizia Charissa Sigalingging; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes Indonesia's efforts to realize the Drug-Free ASEAN 2015. This agreement was made by ASEAN because of drug problems in the South East Asia region have reached the stage of harm. Indonesia as one of the ASEAN member countries is required to realize the agreement by taking some effort to combat drugs.The writer collect data from journals, books, reports, working papers and online media to see how the efforts of Indonesia to realize the Drug-Free ASEAN 2015. The theoretical framework applied in this research are pluralism perspective from Paul R. Viotti and Mark V. Kauppi and foreign policy theory from James N. Rosenau namely adaptive model. Adaptive model focus on how states respond the actions or developments in the international world based on the opportunities and responsibilities of national interest. This model focuses on the process of adaptation actions of a country as a response to changes in the external and internal environment.This research shows that Indonesia's efforts to realize the Drug-Free ASEAN 2015 is take some actions both internally and externally to combat drug problems. In the implementation of this effort, Indonesia also faces a number of challenges. Therefore, Indonesia should should make greater efforts to realize the Drug-Free ASEAN 2015Keywords: Indonesia, Drugs, Efforts, Drug-Free ASEAN 2015